The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1557/jmr.2015.111
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microstructure and mechanical properties of continuous and pulsed current gas tungsten arc welded superaustenitic stainless steel

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Zambon et al 4 and Sathiya et al 16 used CO 2 laser while Devendranath et al 14 employed flux assisted Nd: YAG laser to weld 904L plates, but all researchers reported that the depth of weld penetration (DOP) attained was only 5 mm. The same result was reported by Devendranath et al 17 when continuous and pulsed current gas tungsten arc welding was used to fabricate 904L joints. Devendranath et al 18 studied friction welding of 904L and reported that during fatigue testing, cleavage type fracture was observed.…”
Section: Introductionsupporting
confidence: 81%
“…Zambon et al 4 and Sathiya et al 16 used CO 2 laser while Devendranath et al 14 employed flux assisted Nd: YAG laser to weld 904L plates, but all researchers reported that the depth of weld penetration (DOP) attained was only 5 mm. The same result was reported by Devendranath et al 17 when continuous and pulsed current gas tungsten arc welding was used to fabricate 904L joints. Devendranath et al 18 studied friction welding of 904L and reported that during fatigue testing, cleavage type fracture was observed.…”
Section: Introductionsupporting
confidence: 81%
“…2 AISI 904L is a premium variant of SASS grade with traces of carbon and is well known for its advantageous properties like resistance offered to corrosion, pitting crevice, and acid attacks. [3][4][5][6] By utilizing the said properties this special grade steel it can be used for applications including aerospace, marine, defense, and also in petrochemical industries. To take full advantage of the merits of AISI 904L, proper joining methods that too with optimized process parameters have to be used for autogenous joining of this special grade of steel.…”
Section: Introductionmentioning
confidence: 99%
“…9 Continuous current and pulsed current tungsten inert gas welding techniques could be also utilized for fabricating sound welds of AISI 904L plates but material thickness was limited to 5 mm. 5 The main disadvantages with tungsten inert gas (TIG) welding are the excess expenditure incurred for edge preparation and low productivity as multiple passes with filler wire are a must to fill weld grooves in thick metal joining. A comparative study about TIG and A-TIG welding of 904L confirmed that usage of multi-component activated flux increased depth of weld penetration thrice that of conventional TIG welding.…”
Section: Introductionmentioning
confidence: 99%
“…AISI 904L is a kind of super austenitic stainless steel, which has high strength, high hardness, good impact toughness and welding performance with low carbon, high nickel, chromium, and a small amount of copper alloy system [7,8] . The joining of super austenitic stainless steel can be done with several welding process but, for thin sheets previous researches proved that pulsed current micro plasma arc welding provides good mechanical properties without damaging metal sheets [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%